A randomized noninferiority trial of condensed protocols for genetic risk disclosure of Alzheimer's disease. Issue 10 (9th December 2014) - Green, Robert C.; Christensen, Kurt D.; Cupples, L. Adrienne; Relkin, Norman R.; Whitehouse, Peter J.; Royal, Charmaine D.M.; Obisesan, Thomas O.; Cook‐Deegan, Robert; Linnenbringer, Erin; Butson, Melissa Barber; Fasaye, Grace‐Ann; Levinson, Elana; et al.
Abstract: Introduction: Conventional multisession genetic counseling is currently recommended when disclosing apolipoprotein E ( APOE ) genotype for the risk of Alzheimer's disease (AD) in cognitively normal individuals. The objective of this study was to evaluate the safety of brief disclosure protocols for disclosing APOE genotype for the risk of AD. Methods: A randomized, multicenter noninferiority trial was conducted at four sites. Participants were asymptomatic adults having a first‐degree relative with AD. A standard disclosure protocol by genetic counselors (SP‐GC) was compared with condensed protocols, with disclosures by genetic counselors (CP‐GC) and by physicians (CP‐MD). Preplanned co‐primary outcomes were anxiety and depression scales 12 months after disclosure. Results: Three hundred and forty‐three adults (mean age 58.3, range 33–86 years, 71% female, 23% African American) were randomly assigned to the SP‐GC protocol (n = 115), CP‐GC protocol (n = 116), or CP‐MD protocol (n = 112). Mean postdisclosure scores on all outcomes were well below cut‐offs for clinical concern across protocols. Comparing CP‐GC with SP‐GC, the 97.5% upper confidence limits at 12 months after disclosure on co‐primary outcomes of anxiety and depression ranged from a difference of 1.2 to 2.0 in means (all P  < .001 on noninferiority tests), establishing noninferiority for condensed protocols. Results were similar between European Americans and African Americans. Conclusions: These data support the safety of condensed protocols for APOE disclosure for those free of severe anxiety or depression who are actively seeking such information.